(untitled) (Palíndromo, 2018)
Considering the importance and the centrality that the figure of the author or agent presents in Studies related to the investigation of questions of style in works of art, this article aims to reflect on how the historical dimension contributes for the interpretative exercise of cultural productions. As part of our reflection, firstly we present some approaches developed by Ernst H. Gombrich (1984; 2005) in terms of style issues, to later discuss more broadly the unfolding of this historical perspective through Pierre Bourdieus’s auguments in his book The rules of art (2002).